1993
DOI: 10.1002/jcb.240510112
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory interactions involving the proteins of the phosphotransferase system in enteric bacteria

Abstract: Sugar uptake and cytoplasmic inducer generation as well as cyclic AMP synthesis are regulated by the phosphoeno1pyruvate:sugar phosphotransferase system (PTS) in Gram-negative enteric bacteria. In these organisms, the free form of the glucose-specific Enzyme IIA (IIAg") of the PTS, which can be phosphorylated on a histidyl residue by PEP and the PTS energy coupling proteins, inhibits the activities of non-PTS carbohydrate permeases and catabolic enzymes. By contrast, the phosphorylated form of llAgrC appears … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
36
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 36 publications
1
36
0
Order By: Relevance
“…The PTS consists of a protein phosphoryl transfer chain including two energy coupling proteins or protein domains, enzyme I and HPr, as well as the sugar-specific proteins, enzymes II (29). The PTS also functions in several regulatory capacities (1,25,26,30). In gram-positive bacteria, HPr is phosphorylated by an ATP-dependent, fructose-1,6-bisphosphate (FBP)-activated kinase on a seryl residue, serine 46, as well as by the PEPdependent, enzyme I-catalyzed reaction which derivatizes a histidyl residue, histidine 15 (14,18).…”
mentioning
confidence: 99%
“…The PTS consists of a protein phosphoryl transfer chain including two energy coupling proteins or protein domains, enzyme I and HPr, as well as the sugar-specific proteins, enzymes II (29). The PTS also functions in several regulatory capacities (1,25,26,30). In gram-positive bacteria, HPr is phosphorylated by an ATP-dependent, fructose-1,6-bisphosphate (FBP)-activated kinase on a seryl residue, serine 46, as well as by the PEPdependent, enzyme I-catalyzed reaction which derivatizes a histidyl residue, histidine 15 (14,18).…”
mentioning
confidence: 99%
“…These have crr homologues as part of sugar-specific enzyme IIABC permeases that solely appear to fulfil transport function (F. Titgemeyer, unpublished data; [30][31][32]). For Gramnegative species a multiple role of IIA Glc has been documented and proposed [9,13,14,29].…”
Section: Discussionmentioning
confidence: 99%
“…It appears that glucose kinase serves a global regulatory function, but how it senses and transmits carbon source signals is unclear. It has been demonstrated that IIA Glc of E. coli senses C-regulatory signals from both PTS and non-PTS carbon sources and responds via its phosphorylation state [9,13]. It would be of great interest to examine whether IIA Crr of S. coelicolor operates in a similar way.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations